If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 59 = 4x + 7 Reorder the terms: 59 = 7 + 4x Solving 59 = 7 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 59 + -4x = 7 + 4x + -4x Combine like terms: 4x + -4x = 0 59 + -4x = 7 + 0 59 + -4x = 7 Add '-59' to each side of the equation. 59 + -59 + -4x = 7 + -59 Combine like terms: 59 + -59 = 0 0 + -4x = 7 + -59 -4x = 7 + -59 Combine like terms: 7 + -59 = -52 -4x = -52 Divide each side by '-4'. x = 13 Simplifying x = 13
| 3z+10=-2z+6 | | logx(3x^2-4x-6)=2 | | 2x+14=7x-6 | | m^2-4m=10 | | 3y-2=18-y | | -x-19=15-3x | | (4x+1)(x-5)= | | .4x+13.5*.6=10 | | 4x^3y^2+8xy-12x^3y=0 | | 121-6x=-55+5x | | 3x-9+2x-3=6x+12-8 | | x(4+5)=5(x-2) | | 3(x+1)+6=-12 | | 121-6x=-55+5 | | 12-2m+5=-5 | | ax+7y=8 | | 3(x+0.1)-4(x-0.5)=5.4 | | -2y-5=y+4 | | 3d-11-7d=5 | | 3(x+0.1)-4(x-0.5)=54 | | 5(m-2)=8(m-2) | | log[2](3x+6)=4 | | 5x(x+5)=0 | | y=(x^2-5)(x^2-x^3) | | x=7i | | 152=-3+5(1+6n) | | -148=3(4+4x)+8x | | (4x+2)-(3x-3)=8 | | -11=x-18 | | (17/30)/(3)=z | | (17/30)/(1/3)=z | | 0=-16t^2+128-256 |